How many people can the earth support? - Cohen, Joel E. (New York : Norton, 1995)
Past attempts to answer this question have ranged widelyfrom less than 1 billion to more than 1,000 billion - one sign that there is no single right answer. More than half of the estimates, however, fall within a much narrower range: between 4 billion and 16 billion. In any case, with the world population now at 5.7 billion, and increasing by approximately 90 million per year, we have clearly entered a zone where limits on the human carrying capacity of the Earth have been anticipated, and may well be encountered.
In this penetrating analysis of one of the most crucial questions of our time, a leading scholar in the field reviews the history of world population growth and gives a refreshingly frank appraisal of what little can be known about its future. In the process, he offers the most comprehensive account yet available of how various people have tried to estimate the planet's human carrying capacity. Few contemporary writers have addressed the issue of world population growth in such a balanced, objective way, without using it as a pretext to advance a prior political agenda.
Pt. 1. Introduction. 1. Between Choices and Constraints -- Pt. 2. Past Human Population Growth. 2. Four Evolutions in Population Growth. 3. People Control the Growth of Nonhuman Populations. 4. People Control the Growth of Human Populations. 5. Human Population History in Numbers and Graphs. 6. The Uniqueness of the Present Relative to the Past -- Pt. 3. Future Human Population Growth. 7. Projection Methods: The Hazy Crystal Ball. 8. Mathematical cartoons of human population size and carrying capacity.
Includes bibliographical references (p. [481]-504) and index.
Keywords: Population density; Population -- Economic aspects; Population forecasting